Uji Aktivitas Antibakteri Hasil Fermentasi Bakteri Endofit Umbi Talas (Colocasia esculenta L) terhadap Bakteri Pseudomonas aeruginosa : Potential of Antibacterial Compound Fermentation of Endophytic Bacteria from Taro Tuber (Colocasia esculenta L.) againts Pseudomonas aeruginosa - Desi Purwaningsih; Destik Wulandari (Jurnal Sains dan Kesehatan, 2021)
Bacterial endophyte is an endosimbiont which lives within host plans without causing apparent disease on its host plans. Some endophytic bacteria found in plants have the capability to produce potential compounds as antibacterial. This study aimed to determine the antibacterial activity of the endophytic bacteria fermentation from the tubers of taro plants and determine the optimum time of fermentation which produce the highest antibacterial activity. This research was initially started by producing the suspension of the endophytic bacteria and test bacteria. The suspension that had been made then was used to characterize and identify the endophytic bacteria and test bacteria. Identification methods include colony identification, Gram staining, Spore staining and biochemical tests planted on MCH, SIM, LIA and Citrate mediums. The fermentation was then carried out to produce secondary metabolite compounds which were utilized to examine the antibacterial activity against Pseudomonas auriginosa. The antibacterial activity test was conducted by the disk diffusion assay. The results of the antibacterial activity assay showed that Bacillus siamenssis and Bacillis subtilis were both able to produce secondary metabolites that have potential as antibacterial against Pseudomonas earuginosa. The highest value was achieved by 72 hours fermentation time with a value of 8.7 by Bacillus siamensis. The endophytic bacteria Bacillus subtilis had the highest activity value at 48 hours fermentation time with an average of diameter of inhibition zone of 8.97.